(untitled) - Ross, Stephen A. (Chicago, 1996)
The book provides the modern fundamental of the theory of finance and mkes the theory come to life with contemporary examples. It presents both the theory and practice of corporate finance as the working of a small number of integrated and powerfull intuitions. All of the example, tables, and figures in the book have been edited to include the most up-to-date revision in laws, regulations, and data.
Keywords: Corporations; Finance